Relación entre ansiedad e intolerancia a la incertidumbre en adolescentes - Lau Mora, Sara Inés (2024)
Anxiety, emotion that prepares us for future negative events, is one of the most common mental health problems in adolescence. Intolerance of uncertainty (IU), conceptualized as the dispositional inability to tolerate uncertainty, is associated with anxiety, however, most research focus on adults. The aim of this review is to identify the relationship between anxiety and intolerance of uncertainty in adolescents. To achieve this, articles were selected from Scopus, APA PsycNet, Scielo and Web of Science databases following inclusion and exclusion criteria (n = 10). It was found that there was a positive correlation between anxiety and IU in adolescents, and a possible mediating and predictive function of IU on anxiety. Furthermore, differences were observed in clinical and non-clinical populations, and in the strength of the association with specific anxiety subtypes. It is recommended to incorporate the IU component in interventions focused on adolescent anxiety and to carry out more specific research.